Sociologie des relations ethniques entre descendants des Africains et des coolies dans la littérature mauricienne à l’époque coloniale et postcoloniale - Ramharai, Vikram (Romanica Silesiana)
This article uses Mauritian fiction in French language to analyse the relationship between the slave descendants, the Creoles, and those of the Indian community. Slaves were brought in Mauritius by the French between 1715 and 1810 and the Indians by the British between 1810 and 1925. The interaction (or the absence of interaction) between these two ethnic groups provides fresh insight into the social history of Mauritius and how these two groups (Creoles and Indians) did not mingle with each other. In fact, such interaction could bring a change in the mindset of the people and chaos in society. Colonial novelists’ display of both the Creoles and the Indo‑Mauritians justifies the colonial ideology, whereas that of the postcolonial writers questions this ideology in their writings. Key words: Mauritius, colonial literature, postcolonial literature, Creoles, Indian immigrants